2018
DOI: 10.1002/jper.16-0569
|View full text |Cite
|
Sign up to set email alerts
|

Dental prostheses and tooth‐related factors

Abstract: Objectives: This narrative review summarizes the current evidence about the role that the fabrication and presence of dental prostheses and tooth-related factors have on the initiation and progression of gingivitis and periodontitis.Findings: Placement of restoration margins within the junctional epithelium and supracrestal connective tissue attachment can be associated with gingival inflammation and, potentially, recession. The presence of fixed prostheses finish lines within the gingival sulcus or the wearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 153 publications
0
18
0
2
Order By: Relevance
“…Like any other dental restorations, crowns in the oral cavity tend to create microbial plaque within the gingival crevice primarily due to improper oral hygiene, or other reasons such as inaccurate tooth preparation or ill-fitting prostheses [8]. Consequently, this leads to the development of specific oral infections called periodontal diseases, if untreated, may lead to crown failure and eventual tooth loss [8]. Periodontal inflammation is caused by the adhesion of anaerobic microorganisms such as Porphyromonas gingivalis, Tannerella forsythia and Treponema denticola [9].…”
Section: Introductionmentioning
confidence: 99%
“…Like any other dental restorations, crowns in the oral cavity tend to create microbial plaque within the gingival crevice primarily due to improper oral hygiene, or other reasons such as inaccurate tooth preparation or ill-fitting prostheses [8]. Consequently, this leads to the development of specific oral infections called periodontal diseases, if untreated, may lead to crown failure and eventual tooth loss [8]. Periodontal inflammation is caused by the adhesion of anaerobic microorganisms such as Porphyromonas gingivalis, Tannerella forsythia and Treponema denticola [9].…”
Section: Introductionmentioning
confidence: 99%
“…5,10 Não obstante, esta classificação abrange ainda outras condições capazes de afetar o complexo periodontal, nomeadamente lesões endo-periodon-tais; doenças sistémicas; deformidades mucogengivais (surge um modelo de classificação com 3 tipos de recessão gengival com base no CAL interdentário); forças oclusais traumáticas; fatores locais, relacionados com os dentes e/ ou elementos protéticos. [17][18][19] Ao ser introduzido um novo sistema de classificação, quer a nível universitário quer a nível de prática clínica, é necessário haver um período de adaptação aos novos conceitos que são introduzidos. É, portanto, necessário analisar e planear a aplicação do sistema de classificação que está a ser implementado, o que acarreta tempo despendido para ser efetuada, de forma correta, uma reestruturação do pensamento.…”
Section: Discussionunclassified
“…Recent investigations concluded that tooth loss, tooth mobility, and other complications in patients with RPDs might be decreased by suitable supportive care and a scheduled follow-up of at least six months [ 14 16 ]. Even for fixed restorations, appropriate instructions, periodontal maintenance, and self-motivation for plaque control are essential to avoid negative effects on the periodontium [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%